The impact of COVID-19 and access to health services in the Hispanic/Mexican population living in the United States - Rangel Gómez, María Gudelia; Alcocer Varela, Jorge; Salazar Jiménez, Saúl; Olivares Marín, Leonardo; Rosales, Cecilia (Frontiers in Public Health, 2022)
The United States is home to 10.5 million undocumented immigrants, and about 5 out of 10 are Mexican or Central American. Their immigration status is an obstacle to securing employment that provides labor benefits such as sick and annual leave as well as health insurance. Combine these barriers with a global pandemic, mental and health outcomes impact this vulnerable population as they lack health insurance coverage. Moreover, fear of accessing hospitals or primary care within the U.S. health care system, further exacerbates health and mental wellbeing. The Ventanillas de Salud (VDS) -Health Windows- introduced in 2003 by the Mexican government and housed within the Consular network in the United States, and the Mobile Health Units (UMS) of the Mexican Section of the United States-Mexico Border Health Commission (CSFMEU) since 2016, served to mitigate the impact of this pandemic. The development of this infrastructure presaged the COVID-19 events of the last two years. Both programs have become an important source to support access to health services for the immigrant community by providing basic health screening, referral to health units, COVID19 education, and vaccination services. Between January 2020 and July 2021, the VDS and UMS have provided 11.5 million individual services to just over 4.3 million people.